2021
DOI: 10.3390/app11041514
|View full text |Cite
|
Sign up to set email alerts
|

An Efficiency Enhancing Methodology for Multiple Autonomous Vehicles in an Urban Network Adopting Deep Reinforcement Learning

Abstract: To reduce the impact of congestion, it is necessary to improve our overall understanding of the influence of the autonomous vehicle. Recently, deep reinforcement learning has become an effective means of solving complex control tasks. Accordingly, we show an advanced deep reinforcement learning that investigates how the leading autonomous vehicles affect the urban network under a mixed-traffic environment. We also suggest a set of hyperparameters for achieving better performance. Firstly, we feed a set of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Here, λ was defined as the GAE-lambda hyperparameter, which was a measure of the degree of the dependence on the current-value estimate for calculating updated-value estimates. [18,89] The high and low values of the λ were associated with the strong and weak degrees of the dependence on current-value estimates (high bias, low variance)/actual rewards from the environment (low bias, high variance), respectively. Moreover, a difficulty emerged from the trade-off between the bias and variance, and finding an optimal value of the λ facilitated the training process.…”
Section: Methodsmentioning
confidence: 99%
“…Here, λ was defined as the GAE-lambda hyperparameter, which was a measure of the degree of the dependence on the current-value estimate for calculating updated-value estimates. [18,89] The high and low values of the λ were associated with the strong and weak degrees of the dependence on current-value estimates (high bias, low variance)/actual rewards from the environment (low bias, high variance), respectively. Moreover, a difficulty emerged from the trade-off between the bias and variance, and finding an optimal value of the λ facilitated the training process.…”
Section: Methodsmentioning
confidence: 99%
“…Tran and Bae (2021) present an advanced deep RL technique in [ 3 ] that investigates the impact of leading autonomous vehicles in a mixed-traffic scenario on the urban network. They propose a set of hyperparameters to improve the performance of deep RL agents.…”
Section: Literature Surveymentioning
confidence: 99%
“…Research has demonstrated the effectiveness of using a multi-agent approach for vehicle routing in studies [ 3 , 12 ]. Furthermore, studies [ 7 , 8 , 10 ] have shown the effectiveness of using RL for learning in complex systems like cooperative driving.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…A framework using convolutional neural networks for prediction of time consumption at intersections was proposed, enabling optimal passing order and continuous control for connected vehicles [27]. The impact of leading autonomous vehicles on urban networks was investigated, showcasing potential congestion mitigation benefits [28]. A DRL-based reference speed-planning strategy was introduced for hybrid electric vehicles, with the goal of optimizing fuel economy and enhancing driving safety [29].…”
Section: Introductionmentioning
confidence: 99%